South Africa’s governance and growth challenge - Jeffrey Herbst (2014)
South Africa, once the most advanced African state, has fallen behind its neighbours in economic growth. Its welfare system is also placing undue strain on its revenue base. Is South Africa on an economic decline? Is more effective government part of the answer?